A prospective cohort study of vertical pressure on hands of sitting volleyball players using tekscan pressure mat. Issue 2 (20th January 2011) - Zhang, JM; Bader, D; Twycross-Lewis, R; Padhiar, N
Abstract : Introduction: Current sports medicine knowledge of sitting volleyball injuries in the UK is poor. This prospective pilot study looks at vertical pressures exerted on the hands of sitting volleyball players in controlled movements and compares them to a prospective survey of blister incidences. Method: The pilot study was conducted in Mile End Hospital, London. Using Tekscan F-mat 3150, the researcher recorded peak vertical pressure on volunteer sitting volleyball players. 12 months prospective survey collected demographic data and blister incidences on player volunteers. Results: Data from pressure readings generated a geographical model of typical peak pressures on the hand. The data from the prospective survey generated a geographical map of blister hotspots. The locations of peak vertical pressure correlated with blister hotspots on the hands. Pressure readings from the small volunteer group showed highest peak pressure reading over the proximal aspect of the palm-hypothenar eminence. Real time trajectory of the centre of force was between pisiform and scaphoid of the thenar hypothenar eminences in large portion of the real time trajectory path before transferring to the 2nd and 3rd fingers via the metacarpalphalangeal joints. The lack of recruitment numbers for the pressure readings reduced the accuracy of the data such that the results were more descriptive in nature. Conclusion: Indication from this pilot study suggests that sitting volleyball hand movements can be assessed using gait analysis techniques with a pressure sensitive mat. Further research is recommended.